Burn wound healing and treatment: review and advancements. Issue 1 (December 2015) - Rowan, Matthew; Cancio, Leopoldo; Elster, Eric; Burmeister, David; Rose, Lloyd; Natesan, Shanmugasundaram; Chan, Rodney; Christy, Robert; Chung, Kevin
Abstract Burns are a prevalent and burdensome critical care problem. The priorities of specialized facilities focus on stabilizing the patient, preventing infection, and optimizing functional recovery. Research on burns has generated sustained interest over the past few decades, and several important advancements have resulted in more effective patient stabilization and decreased mortality, especially among young patients and those with burns of intermediate extent. However, for the intensivist, challenges often exist that complicate patient support and stabilization. Furthermore, burn wounds are complex and can present unique difficulties that require late intervention or life-long rehabilitation. In addition to improvements in patient stabilization and care, research in burn wound care has yielded advancements that will continue to improve functional recovery. This article reviews recent advancements in the care of burn patients with a focus on the pathophysiology and treatment of burn wounds.